In-situ formation of BN layers by nitriding boron powders in BN/Si3N4-based composite ceramics. Issue 9 (15th June 2018) - Tang, Xueyuan; Li, Yongwei; Cheng, Xuan; Zhang, Ying
Abstract: Boron nitride/silicon nitride (BN/Si3 N4 ) composite ceramics were fabricated via the in-situ nitridation of boron (B) and silicon (Si) powders in forming gas (95%N2 /5%H2 ) at 1390 °C. The effect of the B content on the phase composition, microstructure, density/porosity, machinability as well as mechanical properties of nitridized BN/Si3 N4 composite ceramics was investigated. The addition of B slightly increased the nitridation degree of the Si and B powders mixture, and improved the ratio of the β-Si3 N4 phase significantly at low B contents. B powders may have acted as a nucleating agent to promote the formation of β-Si3 N4 crystals. A core-shell Si3 N4 /BN structure was revealed by the TEM technique, and the number of BN layers increased with the increase of the B content. The in-situ BN formed by the nitridation of B played a similar role with the BN directly added in enhancing the machinability of the BN/Si3 N4 composite ceramics. The method of the in-situ nitridation of B is also effective to prepare SiC fiber-reforced BN/Si3 N4 ceramic matrix composites.